Association between fatty acids intake and bone mineral density in adolescents aged 12-19: NHANES 2011–2018 - Wang, Zhi-Gang; Fang, Ze-Bin; Xie, Xiao-Li (Frontiers in Endocrinology, 2024)
The relationship between the intake of dietary fatty acids (FA) and bone mineral density (BMD) has been the subject of prior investigations. However, the outcomes of these studies remain contentious. The objective of this research is to examine the link between dietary FA consumption among adolescents and BMD.Methods: This study utilized high-quality data from the National Health and Nutrition Examination Survey database, spanning 2011 to 2018, to explore the association between dietary fatty acids and bone health indicators in adolescents, including BMD and bone mineral content (BMC). Analyses were performed using weighted multivariate linear regression models, incorporating detailed subgroup analysis.The study included 3440 participants. Analysis demonstrated that intake of saturated fatty acids (SFA) was positively correlated with total BMD, left arm BMD, total BMC, and left arm BMC. Monounsaturated fatty acid (MUFA) intake was positively correlated with BMC across most body parts, though it showed no correlation with BMD. Intake of polyunsaturated fatty acids (PUFA) was significantly inversely correlated with both BMD and BMC in most body parts. Additionally, subgroup analysis indicated that variables such as sex, age, standing height, and race significantly influenced the correlation between FA intake and BMD.Our study indicates that dietary intake of SFA may benefit to BMD in adolescents, in contrast to PUFA and MUFA. Therefore, we recommend that adolescents maintain a balanced intake of SFA to promote optimal bone mass development while preserving metabolic health. research leveraged 删除[mes]: of exceptional quality 删除[mes]: covering the years 删除[mes]: investigate the relationship 删除[mes]: The analysis was conducted 删除[mes]: 字体: (中文)宋体, (中文)中文(简体) 设置格式[mes]: and included a 删除[mes]: It showed that 删除[mes]: intake 删除[mes]: There was a positively correlated effect between monounsaturated fatty acids (MUFA) intake and BMC in most body parts, but no correlation with BMD 删除[mes]: